Preferential infiltration of interleukin‐4‐producing CXCR4+ T cells in the lesional muscle but not skin of patients with dermatomyositis. (July 2014) - Fujiyama, T.; Ito, T.; Ogawa, N.; Suda, T.; Tokura, Y.; Hashizume, H.
Summary Dermatomyositis (DM) and polymyositis (PM) are collectively termed autoimmune myopathy. To investigate the difference between muscle‐ and skin‐infiltrating T cells and to address their role for myopathy, we characterized T cells that were directly expanded from the tissues. Enrolled into this study were 25 patients with DM and three patients with PM. Muscle and skin biopsied specimens were immersed in cRPMI medium supplemented with interleukin (IL)‐2 and anti‐CD3/CD28 antibody‐conjugated microbeads. The expanded cells were subjected to flow cytometry to examine their phenotypes. We analysed the cytokine concentration in the culture supernatants from the expanded T cells and the frequencies of cytokine‐bearing cells by intracellular staining. There was non‐biased in‐vitro expansion of tissue‐infiltrating CD4+ and CD8+ T cells from the muscle and skin specimens. The majority of expanded T cells were chemokine receptor (CCR) type 7–CD45RO+ effecter memory cells with various T cell receptor (TCR) Vβs. The skin‐derived but not muscle‐derived T cells expressed cutaneous lymphocyte antigen (CLA) and CCR10 and secreted large amounts of IL‐17A, suggesting that T helper type 17 (Th17) cells may have a crucial role in the development of skin lesions. Notably, the frequency of IL‐4‐producing chemokine (C‐X‐C motif) receptor (CXCR)4+ Th2 cells was significantly higher in the muscle‐derived cells and correlated inversely with the serum creatine phosphokinase (CPK) and lactate dehydrogenase (LDH) levels. stromal‐derived factor (SDF)‐1/CXCL12, a ligand for CXCR4, was expressed at a high level in the vascular endothelial cells between muscular fasciculi. Our study suggests that T cell populations in the muscle and skin are different, and the Th2 cell infiltrate in the muscle is associated with the low severity of myositis in DM.